Osteomeniscal Impact Edema (OMIE): Description of a Distinct MRI Finding in Displaced Flap Tears of the Medial Meniscus, with Comparison to Posterior Root Tears - Krych, Aaron J.; Wu, Isabella T.; Desai, Vishal S.; Kennedy, Nicholas I.; Littrell, Laurel A.; Collins, Mark S.; Saris, Daniël B.F.; Stuart, Michael J. (The Journal of Knee Surgery, 2020)
Bone marrow edema (BME) can be a late finding in osteoarthritis or a sign of subchondral insufficiency. The purpose of this study was to describe the magnetic resonance imaging (MRI) finding we refer to as “osteomeniscal impact edema” (OMIE), or reactive BME adjacent to a displaced meniscus flap tear. In addition, this edema pattern is compared with a control group of medial meniscus posterior root tears (MMPRT) with subchondral insufficiency edema. MRI records from 2000 to 2017 were retrospectively reviewed for studies that showed the presence of a medial meniscus displaced flap tear and an adjacent area of BME. The selected MRIs were matched to an equal number of MMPRT MRI studies. All MRI studies were assessed for cartilage surface grade using the modified Outerbridge classification system and for the extent of accompanying structural abnormalities using the whole-organ magnetic resonance imaging score. Descriptive statistics and hypothesis testing were utilized to compare the MRI findings between groups. Twenty-two flap tear (OMIE group) patients with a mean age of 57 (SD: 15) and 22 root tear (MMPRT) group patients with a mean age of 61 (SD: 10) were included. MRIs in the OMIE group showed a distinctive pattern of focal, peripheral edema adjacent to the meniscus flap tear, compared with more diffuse, central edema in the MMPRT group. Quantitatively, MRIs of the MMPRT group showed significantly worse mean femoral Outerbridge scores (3.72 vs. 2.68, p < 0.0001), more severe central (1.63 vs. 0.5, p = 0.0007) and posterior (0.31 vs. 0.0, p = 0.04) subchondral edema grades, and a higher incidence of tibial subchondral fractures (3 vs. 0, p = 0.036). Meniscus flap tears may present with a distinct MRI pattern of focal, adjacent, peripheral edema, which we refer to as OMIE. Patients with meniscus flap tears showed significantly less arthritic change, lower subchondral edema grades, and a lower incidence of insufficiency fractures and subchondral collapse compared with the diffuse overload edema pattern found with root tears. The Level of Evidence for this study is III.
Keywords: subchondral edema; meniscal root tears; meniscal flap tear; magnetic resonance imaging; knee osteoarthritis; knee arthroscopy